Pengaruh Memorable Tourism Experience Terhadap E-WOM Dimediasi Oleh Destination Attachment: Studi Kasus di Uluwatu Kecak Dance - Ni Luh Putu Pradiayu Aspariyanthi; Ni Ketut Wiwiek Agustina (J-TRUE: Journal of Travel and Leisure, 2024)
The purpose of this research is to investigate the influence of Memorable Tourism Experiences (MTEs) on e-WOM mediated by Destination Attachment (DA). The sample of this study amounted to 180 respondents which are domestic visitors who have visited and posted some photos or videos of their experience about Uluwatu Kecak Dance's performance among their Instagram and Tiktok. Sampling uses purposive sampling technique and data collection by questionnaires distributed via google form. An analysis method called structural equation modelling (SEM) is applied and data of this study used quantitative descriptive. The findings of this study indicate that memorable tourism experience and destination attachment has positive and significant effect on domestic visitor e-WOM behavior. Memorable tourism experience also has a positive and significant impact on e-WOM mediated by destination attachment on Uluwatu Kecak Dance.